2011
DOI: 10.3111/13696998.2011.586621
|View full text |Cite
|
Sign up to set email alerts
|

A short-term cost-effectiveness study comparing robot-assisted laparoscopic and open retropubic radical prostatectomy

Abstract: RALP was more effective and more costly. A way to improve the cost effectiveness may be to perform RALP at fewer high volume urology centres and utilise the full potential of each robot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 15 publications
2
64
0
2
Order By: Relevance
“…Sensitivity analysis using the upper confidence limit for positive margin rate least favourable to robotic prostatectomy (0. 23) showed that robotic prostatectomy would be unlikely to be cost-effective. This value almost identical to that used for laparoscopic prostatectomy (0.24) and the difference (0.01) was lower than the central estimates from other comparative meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analysis using the upper confidence limit for positive margin rate least favourable to robotic prostatectomy (0. 23) showed that robotic prostatectomy would be unlikely to be cost-effective. This value almost identical to that used for laparoscopic prostatectomy (0.24) and the difference (0.01) was lower than the central estimates from other comparative meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…-A retrospective cohort study from Denmark compared costs and outcomes between robotic and open prostatectomy and found the robotic technique to be more costly but more effective with an ICER of €64,343 at one year. This was improved with a higher throughput of cases but cost-utility analysis reporting outcomes as QALYs was not performed [23]. A large cohort study from Sweden also indicated that for robotic prostatectomy case volume is linked to lower risks of positive margin and later biochemical recurrence [24].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were in breast cancer (publication dates 1997 to 2003) (14)(15)(16), seven were in colorectal cancer (publication dates 2000 to 2011) (17)(18)(19)(20)(21)(22)(23) and seven were in prostate cancer (publication dates 2000 to 2012) (24)(25)(26)(27)(28)(29)(30). Two of the three breast cancer studies were set in the United States (14;16), and one was in Norway (15).…”
Section: Resultsmentioning
confidence: 99%
“…One study used the average weighted survival duration (42 months for resected patients) (22). One restricted costs and QALYs to the first post-operative year (25), while one used 5-year retrospective data without extrapolating either costs or benefits (16). Two studies, which limited the perspectives to that of single hospitals, presented incremental benefits over short horizons without extrapolating to account for downstream benefits or costs.…”
Section: Govindarajan 2006(19) Markov Modelmentioning
confidence: 99%
See 1 more Smart Citation